ON AUTOMATIC BOUNDEDNESS OF LINEAR OPERATORS ON CONVEX BORNOLOGICAL SPACES - Tajmouati, Abdelaziz (Italian Journal of Pure and Applied Mathematics, 2014)
In this paper, using the notion of separating space of a linear operator defined on a bornological vector space introduced in [5], we give some useful criteria to study the automatic boundedness of operators. In particular, we give necessary and suﬃcient conditions in order that operators should be bounded (Theorem 3.1 and Theorem 4.1).